Early identification of NORSE and transfer to care setting with appropriate supports: A proposed algorithm - Vinette, Sarah A.; Young, Gordon Bryan; Khosravani, Houman (Frontiers in Neurology, 2023)
New-onset refractory status epilepticus (NORSE) is a presentation where an individual develops refractory status epilepticus without active epilepsy or related neurological conditions. A subset of these individuals has a preceding fever and would be diagnosed with febrile infection-related epilepsy syndrome (FIRES). The underlying etiology of this condition varies and includes autoimmune and viral encephalitides. These conditions require multiple specialized health care teams working collaboratively and numerous resources for investigation of the underlying etiology and management to provide optimal patient care. In this paper, we provide: (1) recommendations for early recognition of NORSE and FIRES, (2) guidance on the resources needed to optimally provide care, and (3) guidance on when to initiate transfer of patients to a more specialized medical center. Additional recommendations for lower-resourced centers without the ability to transfer such patients are also made.